Measuring Rental Housing Affordability of Middle-Income Group in Dhaka City - Jahan, Rowshan; kalam, A K M Abul (Journal of Bangladesh Institute of Planners, 2012)
Providing housing for Dhaka City dwellers is very significant for ensuring sustainable urban development as it is one of the largest growing mega cities in the world. High growth of population in Dhaka city is creating extra pressure on land and making an adverse impact on house rent. The high rental price of housing in Dhaka city makes it impossible for the people, especially middle income group to afford housing. An attempt has made in this research to analyze the existing housing affordability of the middle income group of people in Dhaka city. In this endeavor, a conventional method, the “Rent to Income Ratio Approach Method” is employed to measure affordability and as well as determine the severity of the problem. It reveals that the rent paid for housing varies with income and expenditure of the tenants in different locations. The research observes that access of the middle income group people to housing is constrained by high house rent compared to their income. The paper on the basis of this observation concludes that some measures should be taken to make the housing affordable for middle income group so that they can live in Dhaka city with standard living condition. Journal of Bangladesh Institute of Planners, Vol. 5, Dec 2012, pp. 79-91